Progress and prospect of biomimetic optical materials: A review - Dashuang Wang; Tuo Ping; Zhilan Du; Tingye Liu; Yuxin Zhang (Biogeotechnics)
Recent advances in bionic optical materials (BOMs) are systematically reviewed, emphasizing bioinspired strategies derived from natural models such as plant epidermis, aquatic organisms, avian plumage, and insect photonic architectures (e.g., butterfly wings and inverse opal structures). These biological systems exhibit sophisticated light manipulation mechanisms, including absorption, scattering, and structural coloration, which have guided the design of novel extinction materials with tunable optical properties. By mimicking hierarchical structures and dynamic light-regulation principles, researchers have developed BOMs exhibiting exceptional broadband extinction performance. Notably, applications in optical sensing and imaging systems are critically discussed, highlighting their role in enhancing camera sensitivity and adaptive optical sensor design. Furthermore, this review identifies emerging trends in nanofabrication, machine learning-assisted optimization, and biohybrid material systems. The integration of cross-disciplinary approaches is projected to accelerate the development of multifunctional BOMs, paving the way for breakthroughs in adaptive optics, environmental monitoring, and intelligent photonic devices. In the future, the integration of BOMs and distributed fiber optic sensing technology is expected to realize the whole-life optical monitoring of pile foundation structural health, and promote the development of geotechnical engineering in the direction of intelligence and high precision.